2014
DOI: 10.2961/jlmn.2014.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Laser Printing of Silver Nanoparticles Ink

Abstract: A storage system using fused silica is a promising way to store historically valuable data permanently. To increase recording capacity, we studied the recording and reading conditions for a multilayer sample. The 26-layer sample, which had a recording capacity equivalent to that of a digital versatile disc (DVD), was made with a femtosecond laser and a spatial light modulator (SLM). The recording pulse energy and interlayer crosstalk were reduced by correcting spherical aberration. The sample was evaluated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…That is not an issue for applications such graphic arts and Daetwyler company build a high velocity laser printing prototype to target such applications [97]. However, the printing of conductive track requires a multipass approach to connect the droplets and Rapp et al printed 20 mm width silver lines at velocity up to 4 m/s in three passes [98].…”
Section: D Conductive Structuresmentioning
confidence: 98%
“…That is not an issue for applications such graphic arts and Daetwyler company build a high velocity laser printing prototype to target such applications [97]. However, the printing of conductive track requires a multipass approach to connect the droplets and Rapp et al printed 20 mm width silver lines at velocity up to 4 m/s in three passes [98].…”
Section: D Conductive Structuresmentioning
confidence: 98%
“…Overall, we found that the double layer geometry was the most reliable, with 12 out of 12 1-mm long chains surviving the curing stage, whereas only 6 of 12 1-mm long chains possessing the single layer geometry survived. Chains fabricated by either method possessed a relatively consistent width throughout the entire length of the chain regardless of the stacking geometry, which has proven to be a challenge for low viscosity inks [19,20]. Single-layer and double-layer chains were measured to have an effective resistivity of ∼7.5 × 10 −8 m and ∼9 × 10 −8 m, respectively, roughly 5-6 times the value of bulk silver (1.6 × 10 −8 m) and comparable to the resistivity values quoted by the Ag paste manufacturer, ∼3 × 10 −8 m. [21] As an aside, we refer to this value as "effective resistivity" because it includes the interfacial resistance between voxels, which is a geometric factor and is not intrinsic to the material.…”
Section: Fabrication and Characterization Of Cpwsmentioning
confidence: 99%
“…Actually, the feasibility of printing conductive lines through LIFT has already been proved, both from solid metallic films [12] and from nanoparticle inks [13][14][15][16][17]. In spite that the very small line widths achieved through the LIFT of solid metallic films make this option really attractive in applications requiring very high resolutions, there are still some issues like the presence of splatter or the short length of the printed lines which still limit its industrial implementation.…”
Section: Introductionmentioning
confidence: 98%